In vitro gastrointestinal digestion of polyphenols from different molasses (pekmez) and leather (pestil) varieties. (11th November 2013) - Kamiloglu, Senem; Capanoglu, Esra
Summary In this study, to evaluate the in vitro bioaccessibility of eight different pekmez and pestil samples, total phenolics, flavonoids, proanthocyanidins, anthocyanins and antioxidant capacity were determined at different phases of simulated gastrointestinal (GI) digestion. For the analysis of antioxidant activity, four different methods were used including 2, 2‐azinobis(3‐ethylbenzothiazoline)‐6‐sulfonic acid, 1, 1‐diphenyl‐2‐picrylhydrazil, ferric reducing antioxidant power and cupric ion reducing antioxidant capacity. The results revealed that the dialysed fraction (IN) represented 12–50%, 3–17% and 3–72% of the total phenolics, flavonoids and proanthocyanidins, respectively. Moreover, total antioxidant capacity of IN fraction was 2–57% of the initial values obtained for pekmez and pestil samples. To identify the influence of simulated in vitro GI digestion on total anthocyanins, only black mulberry molasses (pekmez) and plum leather (pestil) were analysed and according to the results no anthocyanins were detected in the IN fraction for both samples. The present study presented a detailed insight of bioaccessibility of polyphenols in various pekmez and pestil samples.